Delicate modulation of mixed conducting properties of PEDOT:PSS via crosslinking with polyvinyl alcohol. (1st December 2022) - Kim, Ji Hwan; Wieland, Matthias; Omiecienski, Beatrice; Kim, Youngseok; Park, Jaeil; Kim, Gunwoo; Ludwigs, Sabine; Yoon, Myung-Han
Abstract: Despite possible toxicity issues, chemical reduction or non-polarizable electrodes incorporated with highly reactive chemical species have been utilized to control the operational characteristics of organic electrochemical transistors (OECTs) for bioelectronic interfacing applications. In this study, we demonstrate that crosslinking between highly conductive poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) and biocompatible nonconductive polyvinyl alcohol (PVA) effectively modulates the mixed conducting properties of PEDOT:PSS. The PEDOT:PSS–PVA films prepared by simple PEDOT:PSS and PVA blending at various ratios, spin-coating, crosslinking, and sulfuric acid treatment were comprehensively studied using optical spectroscopy, x-ray diffraction, atomic force microscopy, and electrical/electrochemical device characterizations. With PVA contents up to 20 wt.%, the resultant PEDOT:PSS–PVA-based OECTs showed a linear threshold voltage shift with a marginal loss of transconductance, suggesting an effective modulation of the peak transconductance gate voltage. Furthermore, the PVA content also affects the ion transport dynamics, which is related to the crystallite size and ionic functional group density in the PEDOT:PSS–PVA system. The detailed mechanism of delicately controlled mixed conduction in the PEDOT:PSS–PVA system is proposed from the perspective of structure-property relations.